Evaluating User Experience of the IPB Help Center Website Using the Usability Testing Method - Hapsari, Helena Dewi; Valenza, Ihsan Lana; Prastyo, Ari Dian; Fami, Amata; Wahyoedi, Bontisesari (Journal of Information System and Informatics, 2024)
The IPB Help Center Website is an essential source for IPB University students to get help in solving technical problems. Research was conducted to evaluate the user experience on the IPB Help Center Website through usability testing methods. This research involved 50 IPB University student respondents who used the IPB Help Center website and filled out a survey through Google Forms. The results showed that the overall level of usability was satisfactory, with high ratings for five usability indicators, including learnability, efficiency, memorability, errors, and satisfaction. The average scores of learnability, efficiency, memorability, errors, and satisfaction indicators are 3.88, 3.95, 3.88, 4.40, and 3.85, respectively. This shows that the IPB Help Center Website has been effective in helping users solve technical problems. This research provides an evaluation to improve the user experience and effectiveness of the IPB Help Center website as a valuable resource for IPB University students. Future research will explore the correlation between various usability indicators to gain further insights.